2014
DOI: 10.1364/ol.39.004349
|View full text |Cite
|
Sign up to set email alerts
|

Super-Gaussian conical refraction beam

Abstract: We demonstrate the transformation of Gaussian input beams into super-Gaussian beams with a quasi flat-top transverse profile by means of the conical refraction phenomenon by adjusting the ratio between the ring radius and the waist radius of the input beam to 0.445. We discuss the beam propagation of the super-Gaussian beam and show that it has a confocal parameter three times larger than the one that would be obtained from a Gaussian beam. The experiments performed with a KGd(WO4)2 biaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…We have explored the influence of ρ 0 over the CR beam and shown that for ρ 0 ≈ 1 both the transverse intensity pattern at the focal plane and the evolution of the beam differs from the CR beam found for ρ 0 ≫ 1, which is characterized at the focal plane by a pair of concentric bright rings with different intensity split by the Poggendorff dark ring. In particular, we have reported the generation of a super-Gaussian beam [68] and a three-dimensional dark focus for ρ 0 = 0.45 and ρ 0 = 0.92 [66], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have explored the influence of ρ 0 over the CR beam and shown that for ρ 0 ≈ 1 both the transverse intensity pattern at the focal plane and the evolution of the beam differs from the CR beam found for ρ 0 ≫ 1, which is characterized at the focal plane by a pair of concentric bright rings with different intensity split by the Poggendorff dark ring. In particular, we have reported the generation of a super-Gaussian beam [68] and a three-dimensional dark focus for ρ 0 = 0.45 and ρ 0 = 0.92 [66], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although being the case of a Gaussian input beam the most studied situation in CR for cylindrically symmetric beams [33,[61][62][63][64][65][66][67][68][69], other works have investigated CR for Laguerre-Gauss beams [70,71] and for top-hat beams [72].…”
Section: Diffractive Solution 221 Cylindrically Symmetric Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The * Corresponding author: alejandro.turpin@uab.cat above named features of CR beams are valid under the assumption that the CR geometrical ring radius R 0 is much bigger than the waist radius of the focused input beam w 0 , i.e., assuming that ρ 0 ≡ R 0 /w 0 ≫ 1. For smaller values of ρ 0 , different light structures are formed [16][17][18].…”
Section: Introductionmentioning
confidence: 99%